2018
DOI: 10.1111/ggi.13326
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of weekend physical rehabilitation for functional recovery in geriatric patients with hip fracture

Abstract: The present cohort analysis showed that weekend rehabilitation for hip fracture patients can lead to functional recovery and reduce the length of stay. Geriatr Gerontol Int 2018; 18: 1143-1146.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Studies have concluded that additional weekend and holiday PT service may possibly reduce hospital LOS for individuals with various disease groups receiving in-patient rehabilitation. 8 , 9 , 10 , 14 , 20 Results of our study are in line with the literature. Results suggested that similar functional mobility ( 0 998 ) and ADL level ( 0 743 ) were achieved with a shorter LOS ( 0 001 ) when patients were discharged from rehabilitation hospital in study group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies have concluded that additional weekend and holiday PT service may possibly reduce hospital LOS for individuals with various disease groups receiving in-patient rehabilitation. 8 , 9 , 10 , 14 , 20 Results of our study are in line with the literature. Results suggested that similar functional mobility ( 0 998 ) and ADL level ( 0 743 ) were achieved with a shorter LOS ( 0 001 ) when patients were discharged from rehabilitation hospital in study group.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Hasebe et al. 14 reported that the additional weekend rehabilitation training led to a faster functional recovery and reduce LOS for Japanese patients with hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Improving Saturday and Sunday AHP services may facilitate an improvement in quality of care in line with the national care guidelines, as well as yield better patient outcomes [8]. Previous research has shown that the availability of weekend physiotherapy services is variable [20], but that these services have the potential to reduce length of stay and improve functional recovery in hip fracture patients [21]. There is also an association between the intensity and frequency of geriatrician input and improved survival of patients with hip fracture [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, however, more high-quality and large-scale trials are needed to identify the optimal rehabilitation regimens, and a tailored mix of different types of training is currently advisable. It should be noted that, when feasible, high-intensity exercise programs have provided more satisfactory health outcomes than lowintensity ones [200][201][202].…”
Section: Physiatric and Physiotherapy Evaluation Individual Rehabilitation Project (Irp) And Early Mobilizationmentioning
confidence: 99%